Aromatic-fused diketophosphanyl-core organic functional materials: phosphorus mimics of imides or beyond?. Issue 34 (17th July 2019) - Takeda, Youhei; Minakata, Satoshi
Abstract : The recent advancement in aromatic-fused diketophosphanyl compounds (phosphorus-analogues of aromatic imides) as organic functional materials is reviewed. Abstract : Recently, missing pieces of organophosphorus compounds, i.e., aromatic-fused diketophosphanyl compounds, have attracted much attention as promising scaffolds of building blocks for functional organic materials. In this review, the brief historical background, synthetic methods, structures, and optoelectronic aspects of aromatic-fused diketophosphanyls are overviewed.